PEMBERANTASAN PENYAKIT PES DI KARESIDENAN PRIANGAN TAHUN 1929-1939 - Sari, Fitriah Ika; Handayani, Sri Ana; Salindri, Dewi (Historia, 2025)
This study discuss the eradication of the plague in the Priangan residency in 1929-1939. The plague in the Priangan Residency emerged and spread due to several factors, so the eradication of the plague had to be carried out in the Priangan Residency. The problems studied in this thesis are the growth and development factors of the plague, the impact caused by the plague, and the control of the plague in Priangan Residency. The method used is the historical method of Louis Gottschalk, namely heuristics, source criticism, interpretation and historiography. This study uses an anthropological approach to health and the theory of Gordon and de le Richt regarding the onset of disease. The plague spreads in Priangan Residency as a result of the plague (Yersinia pestis) as an agent, rat fleas (Xenopsylla cheopis) as vectors or carriers of disease (host), and several other supporting factors so that an environment becomes unfavorable to health. The plague began to appear in the Priangan Residency around 1925 due to several factors, namely the environmental conditions of Priangan which were considered suitable for the development of the plague and vectors, the social and economic conditions of the community, and the negligence of the government which was late in responding to the threat of bubonic plague. With the highest death rate in 1934, which was 20,522 people, the spread of the plague was handled by curative and preventive methods. Curative methods are applied after an infection has occurred, including the fulfillment and improvement of health services, the use of serum and bacteriophages, and treatment of victims. Preventive methods with the aim of preventing the spread of plague are isolation, house repairs, house inspections, building surveillance, vaccinations, and medical propaganda. Thus the plague in Priangan Residency can be overcome.